Mitochondrial ribosome-binding factor A (mtRBFA): mediator of rRNA methylation and maturation - Christian, Brooke E. (Biotarget; Vol 1 (November 2017): Biotarget, 2017)
Mitochondria are organelles perhaps most famous for energy production by oxidative phosphorylation (OXPHOS). In addition to producing ATP, mitochondria are multi-faceted organelles that mediate processes such as autophagy, differentiation, calcium homeostasis, and the immune response (1,2). Mitochondrial dysfunction has been implicated in a number of diseases, including Alzheimer’s disease, Parkinson’s disease, Huntington’s disease, and diabetes, to name a few (3).